PENULISAN BAHASA ASING PADA IKLAN HARIAN PEKANBARU MX - Nengsih Purnama Sari; M.Nur Mustafa; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research has a formulation problem, which is how foreign language is written based on integrity level in daily advertisement of Pekanbaru MX January 2017 edition?. Based on the formulation problem, this research aim to study how foreign language is written based on integrity level in daily advertisement of Pekanbaru MX January 2017 edition. The research method used is a qualitative method that describes the descriptive datas. The data were collected using library research method. Based on data analysis that has been done, 211 data of foreign language consisting of 3 kinds of foreign language which are 2 data of Arabic, 4 data of Mandarin and 205 data of English were found, with the division of 210 data are in first group based on level of integrity and 91 data are in the second group based on the level of integrity.Keywords: Foreign Language, Advertisement, Harian Pekanbaru MX